Digital Impoliteness Strategies in Response to Finance Minister Purbaya’s Assertions on the High-Speed Whoosh Project: A Pragmatic Analysis - Christina Natalina Saragi; Dewi Paulina Silalahi; Nurainun Hasibuan; Renita Br Saragih (JOLLT Journal of Languages and Language Teaching, 2026)
The phenomenon of impoliteness in digital spaces is gaining attention because it can affect the quality of public discourse, especially when it comes to national policy issues. This study aims to analyze the forms of impoliteness strategies used by netizens in responding to the attitude and statements of Finance Minister Purbaya regarding the project. Using a descriptive quantitative method, data was collected from netizen comments on the YouTube platform and classified based on Culpeper's impoliteness taxonomy. The results of the study show a total of 604 occurrences of impoliteness strategies, with positive impoliteness dominating at 37.1% through expressions of belittlement or disrespect. Bald on record impoliteness strategies also appeared significantly, mainly in the form of direct criticism without mitigation (10.76%). Meanwhile, negative impoliteness and sarcasm or mock impoliteness appeared in lower percentages, but still described a consistent pattern of verbal aggression. The results of the study show a total of 604 occurrences of impoliteness strategies, with positive impoliteness dominating at 37.1% through expressions of belittlement or disrespect. Bald on record impoliteness strategies also appeared significantly, mainly in the form of direct criticism without mitigation (10.76%). Meanwhile, negative impoliteness and sarcasm or mock impoliteness appeared in lower percentages, but still described a consistent pattern of verbal aggression. These findings indicate that netizens' responses tend to be evaluative-negative and are often realized through direct attacks on the self-image of public officials. This study concludes that netizens' rudeness is triggered by dissatisfaction with government statements and reinforced by the characteristics of digital communication, which allows for spontaneous expression without strong social control.